Active control for vibration distribution with performance specification and constraints. (15th September 2019) - Wang, Jiqiang
Highlights: Generic problem of vibration distribution is formulated particularly targeting active control of vibration with both suppression and harvesting simultaneously. Vibration distribution is considered for vibrating systems with a networked structure. Active control is achieved via topology feedback. Significant problem of solution existence is answered and used to probe performance limit. Abstract: Vibration control and energy harvesting have been extensively investigated over the past decades. Recent engineering applications motivate a new requirement where vibrations are required to be distributed in a designated specification. This vibration distribution requirement represents a generic problem where both vibration control and energy harvesting need be brought in a par. This paper presents a systematic investigation to this important problem. Fundamental issues associated with vibration distribution under specifications, constraints handling, as well as dynamics and/or topology feedback designs etc are disseminated. Important results are obtained with extensive remarks providing guidance for applications. The corresponding claims are verified through numerical examples.